2019
DOI: 10.3389/fimmu.2019.01800
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the NK Cell Repertoire Related to Initiation of TB Treatment and Onset of Immune Reconstitution Inflammatory Syndrome in TB/HIV Co-infected Patients in Rio de Janeiro, Brazil—ANRS 12274

Abstract: Tuberculosis (TB) is the most common comorbidity and the leading cause of death among HIV-infected individuals. Although the combined antiretroviral therapy (cART) during TB treatment improves the survival of TB/HIV patients, the occurrence of immune reconstitution inflammatory syndrome (IRIS) in some patients poses clinical and scientific challenges. This work aimed to evaluate blood innate lymphocytes during therapeutic intervention for both diseases and their implications for the onset of IRIS. Natural kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 74 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…The median average pairwise distances (APDs) of all proviral sequences was 1.95% (range 0.5%-2.4%), consistent with diverse HIV-1 populations arising after long-term infection (Supplemental Table 1; supplemental material available online with this article; https://doi.org/10.1172/JCI138099DS1). Immunophenotyping of PBMCs showed no major differences between donors and healthy HIV-1-negative controls (25)(26)(27)(28)(29)(30)(31)(32) in the frequencies of T cells, B cells, or NK cells or in expression levels of surface activation markers (CD25, CD69, CD38, and CD107a), with the exception of higher HLA-DR expression (Supplemental Table 3), which is consistent with prior observations in HIV-1-positive individuals on effective ART (33).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The median average pairwise distances (APDs) of all proviral sequences was 1.95% (range 0.5%-2.4%), consistent with diverse HIV-1 populations arising after long-term infection (Supplemental Table 1; supplemental material available online with this article; https://doi.org/10.1172/JCI138099DS1). Immunophenotyping of PBMCs showed no major differences between donors and healthy HIV-1-negative controls (25)(26)(27)(28)(29)(30)(31)(32) in the frequencies of T cells, B cells, or NK cells or in expression levels of surface activation markers (CD25, CD69, CD38, and CD107a), with the exception of higher HLA-DR expression (Supplemental Table 3), which is consistent with prior observations in HIV-1-positive individuals on effective ART (33).…”
Section: Introductionsupporting
confidence: 87%
“…Email: jwm1@pitt.edu. (BD Biosciences) was performed on a BD LSRII cytometer according to standard published methods (58), analyzed using FlowJo (BD), and results compared with published results of healthy adults (25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Concerning natural killer (NK) cells, Pean et al showed that patients with IRIS had a higher proportion of NK cells degranulation levels of these cells were predictive markers of IRIS development among Cambodian TB-HIV co-infected individuals [3]. Our group performed a similar analysis for a subset of patients here included, but no difference was observed in NK degranulation between IRIS and non-IRIS groups [47]. Also, other groups reported elevated frequencies of KIR-γδ T-cells [67] and CD69+ NK cells [68] in TB-IRIS patients during pre-ART, suggesting that these cells may play a role in IRIS-associated pathology.…”
Section: Discussionmentioning
confidence: 86%
“…Patients' enrolment and study design This is a genetic study nested in two clinical and immunological follow-up studies previously conducted in the Laboratory of AIDS and Molecular Immunology (IOC/FIOCRUZ), which assessed immunological characteristics of TB-HIV co-infected individuals and the risk factors for paradoxical TB/HIV-IRIS [32, 46,47]. The HLA-B, HLA-C and KIR genetic profiles were determined from 162 individuals divided into four groups as follows: Group 1 -individuals infected with HIV-1 and tuberculosis (HIV+/TB+ group, n = 88; 11 of them with IRIS); Group 2 -individuals infected with HIV-1 without diagnosis of TB (HIV-1+ group, n = 24); Group 3 -individuals with tuberculosis and seronegative for HIV-1 infection (TB+ group, n = 24); and Group 4 -healthy volunteers without HIV-1 infection and/or TB (control group, n = 26).…”
Section: Methodsmentioning
confidence: 99%
“…This study nested two clinical and immunological follow-up studies conducted in the Laboratory of AIDS & Molecular Immunology (IOC/FIOCRUZ) from 2006 to 2016, as previously described ( da Silva et al., 2013 ; da Silva et al., 2017 ; Giacoia-Gripp et al., 2019 ). All participants signed an informed consent form, and the local ethics committee approved the studies.…”
Section: Methodsmentioning
confidence: 99%